ENGLISH TEACHERS’ EFFICACY IN USING PEDAGOGICAL TECHNIQUES TO PROMOTE HIGHER ORDER THINKING SKILLS - Muhammad Ansori (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
The 21st-century learning demanded students not only to be academically competent but also to master some crucial soft skills needed in today’s challenging world. Promoting and implementing HOTS becomes crucial things to do in the learning process. This study aimed to find out English teachers’ efficacy in using interactive, critical thinking and meta-cognitive pedagogical techniques to promote HOTS in the learning process. This study employed a survey research method. The research approach used is descriptive quantitative. Five Likert-scale questionnaires are used as the instruments for collecting the data. The questionnaires are distributed through the online form to 15 in-service English teachers at the secondary high school level. Furthermore, the data were analysed using a quantitative descriptive data analysis technique. The results of this study indicated that English teachers have high self-efficacy in using interactive, critical thinking, and meta-cognitive pedagogical strategies to promote HOTS in the learning process. The result of this study provides a preliminary understanding about the English teachers’ self-efficacy level in using some meaningful pedagogical techniques to promote HOTS in this 21st-century learning. This understanding will lead to the impact of their implementation in a real teaching context. Exploring their practice in the real classroom context in implementing HOTS becomes a crucial issue for further study.